Factors That Encourage Disclosure of Social Responsibility of Sharia Commercial Banks: A Comprehensive Analysis - Rayhan, Ainun Putri; Tubastuvi, Naelati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research aims to increase public capacity and trust in Islamic commercial banks by using the concept of social responsibility disclosure. The independent variables are profitability as measured by ROA, company size, leverage as measured by DER, the Shia supervisory board size, and financing savings ratio. This research uses secondary data, with data collection using the purposive sampling method, and obtained a sample of 14 Sharia commercial banks in 2017-2022 which were managed using multiple linear regression analysis with SPSS 22 tools. The results of the research show that profitability (ROA) and company size have a positive impact significant to social responsibility disclosure, meanwhile, leverage (DER), size of the Sharia supervisory board, and financing savings ratio do not affect social responsibility disclosure. So, Sharia commercial banks should continue to increase their profitability in disclosing social responsibility because the higher profitability will motivate managers to disclose their social responsibility, the same goes for the size of the company, the higher the size of the company, the greater the number of assets owned by the company. This can expand corporate social responsibility disclosure because companies with large amounts of assets can finance social responsibility information.